Spanish seamen (circular) - Tewson, Vincent
025-0023-001 Telegraphic Address: TRADUNIC, SOWEST, LONDON. Telephone: Victoria 9020. Trades Union Congress GENERAL SECRETARY SIR WALTER CITRINE KBE To whom all communications should be addressed. Department International Our ref. HVT/AC/DT/302 Your ref. TRANSPORT HOUSE, SMITH SQUARE, LONDON, S.W.1. 19th December, 1940. TO SECRETARIES OF CERTAIN TRADES COUNCILS. Dear Mr. SPANISH SEAMEN. It has been decided to make a payment of 5/- per head as a special Christmas Grant to the Spanish seamen. I am incorporating this in this week's remittance and leave it to your discretion whether you distribute it individually to the men or whether you pool it for use in any general local celebration which you may be organising on their behalf. Yours sincerely, H. V. TEWSON, Assistant Secretary. 292/946/25b/19